UTILIZATION OF GROUND GRANULATED BLAST FURNACE SLAG (GGBS) AS AN ENVIRONMENTALLY FRIENDLY PARTIAL REPLACEMENT FOR CEMENT TO IMPROVE CEMENT-BENTONITE EROSION RESISTANCE - Muhammad Akbar Walenna; Zijun Wang; Esdras Ngezahayo (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Cement-bentonite (CB) barriers are frequently employed to mitigate seepage in critical infrastructure such as dams, yet they face persistent challenges from cracking and erosion under hydraulic stresses. Aims: This study aimed to determine whether utilizing ground granulated blast furnace slag (GGBS) as an environmentally friendly partial replacement for cement could enhance the erosion resistance of CB mixtures. Methodology and Results: Laboratory tests were conducted on CB specimens with 0%, 20%, and 50% GGBS replacement, cured for 7, 14, 21, and 28 days. Mechanical integrity was assessed via tensile strength testing, whereas erosion behavior was evaluated using an erosion function apparatus (EFA), measuring erosion rate, critical velocity, and flow parameters. Results revealed that GGBS-modified CB samples experienced a tensile strength increase of up to 180% relative to the control, particularly at extended curing durations. Additionally, the critical velocity necessary to initiate erosion was as much as 94% higher in GGBS-enhanced samples, indicating improved microstructural resilience. Conclusion, significance and impact study: Partial cement replacement with GGBS strengthens CB and improves its erosion resistance, supporting GGBS as a more sustainable binder choice. Scope and limitations: Results are from lab tests on CB mixes (0-50% GGBS; 7-28-day curing; EFA velocity range). Field behaviour can vary with hydraulics, interfaces, and placement; confirm constructability and performance for project conditions.